Cognitive impairment and psychopathology in out-of-hospital cardiac arrest survivors in Denmark: The REVIVAL cohort study protocol - Jacob Eifer Moller; Christian Hassager; Selina Kikkenborg Berg; Ola Ekholm; Trine Bernholdt Rasmussen; Mette Kirstine Wagner; Sophia Armand; Patrick MacDonald Fisher; Gitte Moos Knudsen; Dea Siggaard Stenbæk (BMJ Open)
Introduction Cognitive impairment and psychopathology caused by brain hypoxia and the traumatic impact of critical illness are common in cardiac arrest survivors and can lead to negative consequences of everyday life functioning, and further impact mental health in relatives. Most studies have dealt with the mere survival rate after cardiac arrest and not with long-term consequences to mental health in cardiac arrest survivors. Importantly, we face a gap in our knowledge about suitable screening tools in the early post-arrest phase for long-term risk prediction of mental health problems. This study aims to evaluate the efficacy of a novel screening procedure to predict risk of disabling cognitive impairment and psychopathology 3 months after cardiac arrest. Furthermore, the study aims to evaluate long-term prevalence of psychopathology in relatives.Methods and analyses In this multicentre prospective cohort study, out-of-hospital cardiac arrest survivors and their relatives will be recruited. The post-arrest screening includes the Montreal Cognitive Assessment (MoCA), the Hospital Anxiety and Depression Scale (HADS), the Impact of Event Scale-Revised (IES-R) and the Acute Stress Disorder Interview (ASDI) and is conducted during hospitalisation. In a subsample of the patients, functional MRI is done, and cortisol determination collected. At 3-month follow-up, the primary study outcomes for 200 survivors include the Danish Affective Verbal Learning Test-26 (VAMT-26), Delis-Kaplan Executive Function System tests (trail making, colour-word interference, word and design fluency), Rey’s Complex Figure and Letter-number sequencing subtest of Wechsler Adult Intelligence Scale-IV, HADS and IES-R. For the relatives, they include HADS and IES-R.Ethics and dissemination The study is approved by the local regional Research Ethics Committee (H-18046155) and the Danish Data Protection Agency (RH-2017-325, j.no.05961) and follows the latest version of the Declaration of Helsinki. The results will be published in peer-reviewed journals and may impact the follow-up of cardiac arrest survivors.